2017
DOI: 10.1159/000471893
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Febuxostat on the Endothelial Dysfunction in Hemodialysis Patients: A Randomized, Placebo-Controlled, Double-Blinded Study

Abstract: Background: Endothelial dysfunction is an important risk factor for cardiovascular diseases to occur in end-stage renal disease patients. Febuxostat, being a novel xanthine oxidase inhibitor, is apparently having a beneficial role in improving the endothelial dysfunction; however, data among hemodialysis patients are still limited. Methods: A prospective, placebo-controlled, block-randomized, double-blinded study was carried out to evaluate the effect of oral febuxostat on the endothelial dysfunction in hemodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…This meta-analysis included reducing urate production with xanthine oxidase inhibitors rather than uricosuric increasing uric acid excretion exactly. Xanthine oxidase inhibitors including allopurinol and febuxostat inhibited oxygen species (ROS) formation and also improved several different measures of endothelial dysfunction in CKD [17, 34 ]. Moreover, xanthine oxidase inhibitors may decrease glomerular hydrostatic pressure and alleviate renal damage through reducing uric acid level.…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis included reducing urate production with xanthine oxidase inhibitors rather than uricosuric increasing uric acid excretion exactly. Xanthine oxidase inhibitors including allopurinol and febuxostat inhibited oxygen species (ROS) formation and also improved several different measures of endothelial dysfunction in CKD [17, 34 ]. Moreover, xanthine oxidase inhibitors may decrease glomerular hydrostatic pressure and alleviate renal damage through reducing uric acid level.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model, a previous study demonstrated that a therapeutic dose of febuxostat appropriate for hyperuricemia considerably improved endothelial dysfunction . Alshahawey et al randomized 57 hemodialysis patients into a febuxostat treatment group and control group and followed them over two months. They concluded that febuxostat improved endothelial dysfunction, but they used asymmetric dimethylarginine as the index of endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have proposed that febuxostat is able to ameliorate oxidative stress, as well as to reduce inflammation and enhance insulin sensitivity . It has been also suggested that it presents significant renoprotective properties, since its administration was able to delay chronic kidney disease progression and improve endothelial function in dialysis patients …”
Section: Introductionmentioning
confidence: 99%
“…12 It has been also suggested that it presents significant renoprotective properties, since its administration was able to delay chronic kidney disease progression 13 and improve endothelial function in dialysis patients. 14 Growing interest exists regarding the potential role of febuxostat in the prevention of TLS. However, although several recent studies have investigated its effectiveness, there is no firm consensus concerning whether it should be considered as an alternative to allopurinol.…”
mentioning
confidence: 99%